MANAJEMEN QUR’ANI MENUJU KEMANDIRIAN UMAT - Mulyono, Mulyono (ULUL ALBAB Jurnal Studi Islam, 2010)
Al Quran contains conceptual ideas related to theology (aqidah), worship, human relation (muamalah), science, philosophy, and many others. It includes some regulations to manage the attitude of human beings, both as individuals and as social creatures, for the sake of achieving better future in the world and in the eternal life (akhirat). It is no wonder that al-Qur’an also brings up some basic concepts of management, which are academically acknowledged as al Quran–based Management or Quranic Management. As this paper mainly concerns, al Quran encompasses several verses explaining the concepts of management. It requires Moslems to be autonomous society by planning any actions, preparing and positioning qualified human resources, occupying the assets as well as possible, consolidating the branches, and operating the wealth into beneficial activities. Such an ideal can be straightforwardly accomplished by performing the Quranic Management principles, which comprise amar ma’ruf nahi mungkar, truth, justice, and amanah (trustworthiness).